Perilaku Seksual Siswa Ditinjau dari Durasi Penggunaan Media Sosial TikTok - Rifani, Alfisyah; Mudjiran, Mudjiran (Current Issues in Counseling, 2023)
The surroundings around adolescents, as well as the rapid growth of technology, have a big influence on the background of bad adolescent behavior. The internet and information technology are undeniably tools for creating and disseminating sexual content. Students are caught watching and storing pornographic videos, sharing sexual fantasy stories on social media, flaunting their intimacy with their partners in public, following trends on social media, and engaging in sexual intercourse without realizing the consequences. The duration of social media use is one of the aspects in social media that influence students sexual behavior. The purpose of this study is to characterize students' sexual behavior and the duration of using social media TikTok, as well as to look at differences in sexual behavior between students who use social media TikTok for a long time and students who use it for a short time. This study is a descriptive and comparative study with 123 students, comprising 56 students who use social media TikTok for a long time and 67 students who use social media TikTok for a short time. A questionnaire instrument with a Likert scale was employed in this investigation. The data was analyzed using descriptive statistics and several tests utilizing the t-test procedure. According to the study's findings, there are substantial disparities in the sexual behavior of students who use the social media platform TikTok in terms of duration of use.Keywords: Sexual Behavior, Duration of Social Media Use TikTok